Solving fully randomized higher‐order linear control differential equations: Application to study the dynamics of an oscillator. Issue 6 (20th April 2021) - Cortés, Juan‐Carlos; Navarro‐Quiles, Ana; Romero, José‐Vicente; Roselló, María‐Dolores
Abstract: In this work, we consider control problems represented by a linear differential equation assuming that all the coefficients are random variables and with an additive control that is a stochastic process. Specifically, we will work with controllable problems in which the initial condition and the final target are random variables. The probability density function of the solution and the control has been calculated. The theoretical results have been applied to study, from a probabilistic standpoint, a damped oscillator.